Discriminação contra pessoas cegas: o papel da percepção de ameaça e do preconceito - Santos, Francisca Ádila dos (2022)
People with disabilities have carried negative stigmas since the most primitive societies. However, with the eminence of human rights and the anti-prejudice norm in democratic societies, the expression of discrimination has become subtler. This happens because people have begun to use justifications that disguise the prejudiced nature of their actions, such as the idea that the very existence of the target of those actions is a social threat. We examined this phenomenon in a set of studies on the influence of intergroup threat on discrimination against visually impaired people and wondered whether prejudice towards this group moderates such an influence. To this end, we carried out three experimental studies in which we manipulated intergroup threat (threat salience condition vs. non-salient threat) in a fictitious applicant selection situation (visually impaired vs. non-visually impaired) in a college context (Study 1); and resources (favorable to visually impaired people vs. non-visually impaired people) to be used in education (Studies 2 and 3). In Study 1 (N = 182), we tested our hypotheses on a sample of students enrolled in Brazilian federal universities. In Study 2 (N = 121), we repeated the procedure on a sample of elementary school teachers. In Study 3 (N = 234), we extended the results found to a sample of students enrolled in different educational programs. The results obtained in the three studies showed that the threat represented by the mere presence of the visually impaired influences discriminatory behavior toward visually impaired students and, more importantly, that this effect occurs only among participants who are high in prejudice. Among participants who expressed prejudice to a lesser degree, threat familiarity did not significantly influence discrimination. The effects of discrimination against visually impaired individuals are discussed, particularly in the educational context, as well as the importance of reducing prejudice to minimize discrimination that occurs in response to the threat.